Incidence and predictors of cutaneous manifestations during the early course of systemic sclerosis: a 10-year longitudinal study from the EUSTAR database. Issue 7 (31st July 2015) - Wirz, Elina G; Jaeger, Veronika K; Allanore, Yannick; Riemekasten, Gabriela; Hachulla, Eric; Distler, Oliver; Airò, Paolo; Carreira, Patricia E; Tikly, Mohammed; Vettori, Serena; Balbir Gurman, Alexandra; Damjanov, Nemanja; et al.
Abstract : Objectives: To longitudinally map the onset and identify risk factors for skin sclerosis and digital ulcers (DUs) in patients with systemic sclerosis (SSc) from an early time point after the onset of Raynaud's phenomenon (RP) in the European Scleroderma Trials and Research (EUSTAR) cohort. Methods: 695 patients with SSc with a baseline visit within 1 year after RP onset were followed in the prospective multinational EUSTAR database. During the 10-year observation period, cumulative probabilities of cutaneous lesions were assessed with the Kaplan–Meier method. Cox proportional hazards regression analysis was used to evaluate risk factors. Results: The median modified Rodnan skin score (mRSS) peaked 1 year after RP onset, and was 15 points. The 1-year probability to develop an mRSS ≥2 in at least one area of the arms and legs was 69% and 25%, respectively. Twenty-five per cent of patients developed diffuse cutaneous involvement in the first year after RP onset. This probability increased to 36% during the subsequent 2 years. Only 6% of patients developed diffuse cutaneous SSc thereafter. The probability to develop DUs increased to a maximum of 70% at the end of the 10-year observation. The main factors associated with diffuse cutaneous SSc were the presence of anti-RNA polymerase III autoantibodies, followed by antitopoisomerase autoantibodies and male sex. The main factor associated with incident DUs was the presence of antitopoisomerase autoantibodies. Conclusion: Early after RP onset, cutaneous manifestations exhibit rapid kinetics in SSc. This should be accounted for in clinical trials aiming to prevent skin worsening.